INKONSISTENSI PUTUSAN MAHKAMAH KONSTITUSI TERHADAP KEBERADAAN KOMISI PEMBERANTASAN KORUPSI SEBAGAI LEMBAGA NEGARA INDEPENDEN - Theresa Yolanda Sirait; Bintang ME Naibaho; Janpatar Simamora; Leonardo David Simatupang (Nommensen Journal of Legal Opinion, 2020)
The Constitutional Court as mandated in the constitution has a function as a guardian of the constitution, therefore, if there are norms in the Act that against to the 1945 Constitution of the Republic of Indonesia can be done by a trial. The decision of the Constitutional Court in the trial of the Act is related to the formal and material aspects, then the verdict that has been fulfilled the legal considerations by the judge, it will become the basis of a decision. Therefore, the verdict can not revoked arbitrarily unless in making decision due to coercion or negligence. The thesis deals and focuses on two aspects: First, showing and analyzing the considerations of the Constitutional Court in deciding the case No.012-016-019 / PUU-IV / 2006, No.19 / PUU-V / 2017, No.37-39 / PUU-VIII / 2010, No.5 / PUU-IX / 2011, No.36 / PUU-XV / 2017. Second, explains why the Constitutional Court inconsistency in determining the status and legal position of the KPK (Corruption Eradication Commision) through its verdict. From the new latest verdict of the Constitutional Court said that the KPK is an independent state institution under the executive authority , it is different from the previous four Constitutional Court decisions which said KPK as an independent state institution.